Critical current densities and flux creep rates in near optimally doped BaFe2-xRuxAs2 (x≈0.7) single crystals - Haberkorn, Nestor Fabian (2016)
We present an investigation of the critical current densities Jc and flux creep rates in a near optimally doped BaFe2-xRuxAs2 (x≈0.7) single crystal by (measuring magnetization). The superconducting critical temperature is 18 K. The in-field dependences of the critical current density Jc are due to a mixed pinning scenario produced mainly by large precipitates and a less significant contribution of random disorder. Furthermore, a Maley analysis in the regime dominated by strong pinning centers (μ0H=0.1 T) is well described through a glassy exponent μ=1.9 and a collective pinning energy (U0) smaller than 100 K.